(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the frequency of abortion in women of low socioeconomic status of Karachi. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the four hospitals of Karachi, fwo from public and two semi- Government hospitals, namely Jinnah Postgraduate Medical Center, Civil Hospital, Lady Dufferin and Sobraj hospital, Karachi from February to October 2017. Materials and Methods: A cross sectional study was conducted on a sample size of 205 women,that is n=205. The sample was taken through Non-probability purposive sampling from low socio-economic class women from different hospitals of Karachi including Jinnah Postgraduate Medical Center, Civil Hospital, Lady Dufferin and Sobraj hospital, within a period of 9 months from Feburary to October 2017. A structured self administered questionnaire was distributed which was filled after an informed verbal consent from the women. A pilot study was conducted to assess the validity of questionnaire. Data was analyzed using SPSS version 20 with 95% confidence interval, margin of error was taken as 5% and P-value 0.05 was considered significant. Results: A total of 205 women were interviewed through structured questionnaire. The median age of women was between 26-35 years. Family monthly income in (55.6%) was <10,000 Rs and 91 women had income between Rs.11000-17000. 154 women visited the doctor for vaginal bleeding suggesting threatened abortion(75%, p=0.037) 108 women had abnormality of aborted baby showed on Ultra Sound (52.7%, p=0.040) 78 women had infections in 1st trimester of pregnancy (38.0%, p=0.029), 70 had taken capsules (antibiotics) for infection in 1st trimester of pregnancy (34.1%, p=0.040), 64 had trauma (31.2%, p=0.003) 154 women had cervical incompetence (75%, p=0.021) and 76.6% women lifted heavy objects during pregnancy p=0.059. Conclusion: The study concluded frequency of threatened abortion in low socioeconomic status women is high and level of awareness about the causes and risk factors of spontaneous abortion is unsatisfactory. Increased efforts are needed to help both adolescent women and adult women of low socio-economic status to avoid unwanted outcomes of pregnancy. There is a crucial need to take preventive measures in low socioeconomic class to save the health of women and children.